Pengaruh Pola Asuh Orang Tua Terhadap Perkembangan Bahasa Anak Usia Dini - Okma Permata (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The occurrence of language delays in children can result a difficulties in communicating and interacting.Parents play an important role in the development of a child, both physically and linguistically. If the caregiver has good and adequate language and is able to understand the child's development, the child will easily listen to and accept the vocabulary issued or taught by the caregiver.This study aims to look at the description of language development of children through parenting and the influence of the surrounding environment.This study used descriptive qualitative method. The processing and data collection techniques are carried out through observation, interviews and notes.The subjects in this study are two five-year-old boys from the same area with different parenting styles.The location of this research is in Punggung Lading Village, South Pariaman District, Pariaman City. The results of the study show that parenting, direction and guidance from parents play an important role in the development of children's language, because parents are the bridge for children to have broad and good knowledge that will be used and developed in everyday life.